Options for sustaining solar-powered mosquito trapping systems on Rusinga Island, Western Kenya: a social dilemma analysis - Prisca A. Oria; Michiel Wijnands; Jane Alaii; Cees Leeuwis (BMC, 2018)
Abstract Background In 2012, a donor-supported proof of principle study was launched to eliminate malaria from Rusinga Island, western Kenya, using solar-powered mosquito trapping systems (SMoTS). SMoTS, which also provided power for room lighting and charging mobile telephones, were installed in houses. In view of the involvement of individual and collective benefits, as well as individual and collective maintenance solutions, this study qualitatively examined preferences of some project stakeholders towards SMoTS sustainability components to see if and how they related to social dilemma factors. Methods The data were collected through participant observation, semi-structured interviews and focus group discussions. Results The results show that respondents largely preferred individual solutions to various aspects of maintenance. Selective collective solutions such as table banking groups were considered positively for mobilising financial resources for maintenance, but respondents were hardly willing to contribute financially to a collective entity. Few people saw a meaningful role for a collective governing body; people preferred to rely on individual household responsibility and private service delivery for repairs and stocking spare parts. An overriding concern was that people lacked trust in other community members, leaders and/or technicians who would be employed by a governing body. Respondents also had little confidence that a governing body or saving group could effectively impose sanctions to misappropriation of funds, poor leadership, defecting group members or technicians that might abuse a salaried position. Conclusion There seemed to be linkages between preferences towards organising various components of SMoTS sustainability and known hindrances to addressing social dilemmas. This posed considerable challenges to organising the sustainability of this innovative malaria control strategy. Trial registration NTR3496.